2015
DOI: 10.1007/s00520-015-3011-3
|View full text |Cite
|
Sign up to set email alerts
|

How sedentary and physically active are breast cancer survivors, and which population subgroups have higher or lower levels of these behaviors?

Abstract: Interventions to facilitate physical activity and reduce sedentary time among breast cancer survivors should consider comorbidity status and previous PA experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 36 publications
6
73
2
1
Order By: Relevance
“…The full methods have been described previously. (6) Briefly, participants were between two and four years post-diagnosis, between 18 and 80 years of age and residing in WA at the time of diagnosis, and had previously taken part in a case-control study (13). Breast cancer survivors who were currently receiving chemotherapy or radiotherapy, had experienced a recurrence of their breast cancer, or had been diagnosed with another cancer were ineligible.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full methods have been described previously. (6) Briefly, participants were between two and four years post-diagnosis, between 18 and 80 years of age and residing in WA at the time of diagnosis, and had previously taken part in a case-control study (13). Breast cancer survivors who were currently receiving chemotherapy or radiotherapy, had experienced a recurrence of their breast cancer, or had been diagnosed with another cancer were ineligible.…”
Section: Methodsmentioning
confidence: 99%
“…Of those 340 participants, 274 (50% of the 552 eligible breast cancer survivors invited) completed the study. The participants and non-participants did not differ in terms of age, socioeconomic status, breast cancer grade or time since diagnosis (6). Eighteen participants were missing data on one or more of the variables used in this analysis, leaving 256 participants in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The continuum of evidence, from experiments in animals to large population studies, has demonstrated that higher volumes of sedentary behavior are associated with a range of negative physiologic effects, and some effects are thought to be distinct from not performing sufficient moderate-intensity to vigorous-intensity physical activity (MVPA). 11 Sedentary behavior in cancer survivors appears to be high, with accelerometer-based assessment indicating that, on average, cancer survivors spend between 8.2 and 10.8 hours per day sedentary, 12,13 which is higher than the general US National Health and Nutrition Examination Survey population aged ≥60 years. 11 Sedentary behavior in cancer survivors appears to be high, with accelerometer-based assessment indicating that, on average, cancer survivors spend between 8.2 and 10.8 hours per day sedentary, 12,13 which is higher than the general US National Health and Nutrition Examination Survey population aged ≥60 years.…”
Section: Introductionmentioning
confidence: 99%
“…association between fatigue, physical activity, and sleep especially in cancer survivors. [20][21][22] There are also very limited published studies in patients with advanced cancer to describe the association between objectively measured physical activity and subjective symptoms.…”
Section: Introductionmentioning
confidence: 99%